Blockchain Technology and Systemic Risk - Mselmi, Aymen (International Journal of Economics and Financial Issues, 2020)
This paper examines the effect of financial institutions management information system migration to blockchain technology on systemic risk. Our study examines a sample of 40 financial institutions around the world. The aim is to identify to what extent the migration of financial company management information system to blockchain system contribute to minimize systemic risk measures through regressions on panel data. We have reached the empirical evidence which indicates that the change we mentioned earlier affect immediately the systemic risk level. Companies that have adopted the blockchain technology recorded a significant reduction in systemic risk level. In addition, financial institutions that have adopted this latter system recorded a significant decrease in long-run marginal expected shortfall and systemic risk index. Keywords: Blockchain; Systemic Risk, Financial institutions JEL Classifications: G21, G32 DOI: https://doi.org/10.32479/ijefi.9069